Do Massage and Relaxation Music Therapy Increase Breast Milk Volume? A Meta-Analysis - Sakinah, Sakinah; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Journal of Maternal and Child Health, 2023)
Background: Breast milk contains various nutrients that meet the needs of infants’ growth and development. Furthermore, breast milk also contains various antibodies that will protect infants from viruses and bacteria to avoid infections and various diseases. Various conditions encountered by postpartum mothers often lead to stress and anxiety that generate a low milk supply, thus the infants do not get breast milk optimally. This study aims to discover the effect of massage and relaxation music therapy on breast milk volume. Subjects and Method: The study used systematic review and meta-analysis using the PICO model. Population= postpartum mother, Intervention= massage and relaxation music therapy, Comparison= no massage and relaxation music therapy, and Outcome= breast milk volume. Article search was conducted in various databases, namely PubMed, BMC, ScienceDirect, ResearchGate, SpringerLink, and NCBI. The articles were collected in 1 month. The articles were published from 2012-2022. The keywords in this article search were "Massage AND Lactation" OR "Massage AND Milk Production" AND "Music AND Milk Production" OR "Relaxation AND Breastfeeding" AND "Randomized Controlled Trial".   The inclusion criteria were full-text articles with an RCT study design, the correlation size used was mean and SD, and the articles were in English. The articles were analyzed using the RevMan 5.3 application. Results: This study used 14 articles with sample populations from China, India, Indonesia, the United Kingdom, Iran, Malaysia, Thailand, and Turkey. The administration of massage had a positive effect 1.42 times more effective on the increase of breast milk volume compared to without massage (SMD= 1.42; CI 95%= 0.98 to 1.86; p<0.001).  Relaxation music therapy can increase breast milk volume by 0.46 times compared to without relaxation music therapy (SMD= 0.46; 95% CI= 0.31 to 0.60; p<0.001). Conclusion: Massage and relaxation music therapy have a positive effect on the increase of breast milk volume. Keywords: massage, relaxation music therapy, breast milk volume, postpartum. Correspondence: Sakinah. Master’s Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java, Indonesia. Email: sakinah13579@gmail.com. Mobile: +6282386391993.